factorise
a²+b²-2ab-4c²
Answers
Answered by
4
Answer:
Step-by-step explanation:
a²+b²-2ab-4c²
= (a-b)²-4c²
= (a-b)²-(2c)²
Now, this is in the form of x²-y²=(x+y)(x-y)
where, x= a-b and y=2c
Therefore,
= (a-b+2c) (a-b-2c).
Answered by
1
Step-by-step explanation:
hope it helps you......
Attachments:
![](https://hi-static.z-dn.net/files/dee/12deefd09cb74e2f6fd53b8f1da52229.jpg)
Similar questions
Computer Science,
2 months ago
Physics,
2 months ago
Social Sciences,
2 months ago
History,
4 months ago
English,
11 months ago
Math,
11 months ago
English,
11 months ago